(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In the dynamic and demanding field of military education, the professional growth of cadets is paramount for the development of competent and effective military leaders. This article examines the significance of designing personalized educational trajectories for cadets in higher military educational establishments. By tailoring educational experiences to individual needs and career goals, cadets can achieve greater professional growth and readiness for future challenges. The article includes a literature review on personalized education in military contexts, a detailed methodology for designing personal trajectories, and an analysis of the impact on cadet development.